EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN KEPERCAYAAN DIRI (STUDI EKSPERIMEN DI PANTI ASUHAN HIDAYATULLAH PALEMBANG) - Manah Rasmanah; Yeti Nurhayati (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2018)
Self confidence is very important for every individual isn’t exception foster children, because self confidence is needed to achieve success. The research objective is to determine self confidence of foster children between before and after getting group guidance services. This research was using quantitative method that pre experiment design. The discovering of this research are: 1) self confidence before received group guidance service 58.3% in medium category, 2) after received group guidance service 66.6% in medium category, 3) test result wilcoxon signed rank test obtained Zhitung = 2,670 and Ztabel = 1,645 with a significant level of 5% so that Zhitung>Ztabel. So there are difference in the self confidencen level of foster children before and after received group guidance services